Is a model EU BIT possible – or even desirable? - Armand de Mestral C.M. (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The author explores whether the EU is in a position to adopt a model BIT articulating a common policy on FDI.
Keywords: 330